The Fast-Mapping Abilities of Adults With Developmental Language Disorder. - McGregor, Karla K.; Eden, Nichole; Arbisi-Kelm, Timothy; Oleson, Jacob (Journal of Speech, Language & Hearing Research, 2020)
Purpose: The aim of the study was to determine the integrity of fast mapping among adults with developmental language disorder (DLD). Method: Forty-eight adults with DLD or typical language development (TD) were presented with 24 novel words and photos of their unfamiliar referents from the semantic categories of mammal, bird, fruit, or insect in two conditions. In the fastmapping condition, 12 of the 24 unfamiliar referents were presented, one at a time alongside a familiar referent (e.g., a dog) and a question (e.g., Is the tail of the torato up?). In the explicit-encoding condition, the other 12 unfamiliar referents were presented alone, one at a time, with a label (e.g., This is a spimer). Immediately after exposure (T1) and again after a 1-day interval (T2), memory for the word-to-exemplar link was measured with a three-alternative forced-choice test, requiring the participant to match a spoken word to one of three pictured referents from the training set. At T2, memory for semantic category information was measured with a four-alternative forced-choice test, requiring the participant to match a spoken word to one of four prototypical silhouettes representing each of the semantic categories. Results: Performance on word-to-exemplar link recognition was stronger for words learned in the explicit-encoding than the fast-mapping condition and stronger for the TD group than the DLD group. Time was not a significant factor as both groups maintained posttraining levels of performance after a 1-day retention interval. Performance on semantic category recognition was stronger for words learned in the explicit-encoding than the fast-mapping condition and stronger for the TD group than the DLD group. The lower category recognition performance of the DLD group was related to their lower nonverbal IQ scores. Conclusion: Contexts that allow for explicit encoding yield better learning of word-to-referent links than contexts that allow for fast mapping in both stronger and weaker learners. Adults with DLD have difficulty learning the link between words and referents, whether trained via fast mapping or explicit encoding and whether tested with exemplar or category referents. Retention is a relative strength for adults with DLD.